La filosofía como rama de la literatura: entre Borges y Deleuze - Cherniavsky, Axel (ARFIL y UNL, 2018)
Borges’s relationship with philosophy seems to have arisen three questions: Is Borges a philosopher? Which is his philosophy? What does he do with philosophy? However, it isn’t certain that the answers to these questions specify the value of Borges for philosophy. This is a different question, which can’t be answered from Borges’s own work, precisely because it is its philosophical condition what is at stake. Therefore we propose to do it from the history of philosophy and philosophical discourse theory of Gilles Deleuze. Indeed, we believe that it is possible to find here a new way of interpreting Borges’s famous sentence according to which philosophy would be a branch of literature.